Let's simplify step-by-step To understand :)
3x2−7x−(x2+3x−9)
Distribute the Negative Sign:
=3x2−7x+−1(x2+3x−9)
=3x2+−7x+−1x2+−1(3x)+(−1)(−9)
=3x2+−7x+−x2+−3x+9
Combine Like Terms:)
=3x2+−7x+−x2+−3x+9
=(3x2+−x2)+(−7x+−3x)+(9)
=2x2+−10x+9
Answer :)
=2x2−10x+9
HOPE THIS HELPS
Answer: 5,0 6,1 7,2 9,4 11,6
Step-by-step explanation:
Answer:
x = -15 and x = 1
Step-by-step explanation:
Since we have to use the complete the square method, we first need to <u>rewrite the equation</u> in the form
.
This results in
.
Next, we <u>simplify the equation</u> to get
.
<u>Factoring </u>the left side gives us
.
Finally we <u>solve the equations</u>:
and
.
This gives us x=1, and x=-15
Answer: Maggie is 29 years old
Step-by-step explanation:
12*3=36
36-7=29
29 + 12 = 41
put ur ASSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSSS IN UR FATHER